ANALYSIS OF TEA HARVESTING MECHANIZATION (CAMELLIA SINENSIS) ON THE INCOME OF PICKING WORKERS IN WONOSOBO TEA PLANTATIONS, CENTRAL JAVA - Githa Noviana; Fani Ardiani; Purwadi Purwadi; Santa Monica; Idum Satia Santi (ITScience (Information Technology and Science), 2022)
Indonesia is one of the largest tea producing countries where dry tea production is exported to various countries. The tea industry absorbs a lot of labor both from the area around the tea garden and from outside the garden area. Tea pickers are workers who really need their existence, considering the quality and quantity of tea depends on how they work. The wages of tea pickers are very low due to the small amount of picking weight produced because the picking system is still done manually. The purpose of this study was to determine the effect of manual picking mechanization and using scissors on the wages earned by pickers. Sampling was done randomly and analyzed using multiple linear regression. The results showed that there was a significant difference between the picking system and the wages of the pickers. The use of picking scissors can increase wages by 40.18%. The increase in pickers' income is expected to be able to motivate pickers to work optimally to increase the welfare of Wonosobo tea pickers.